Journal Info - Board, Editorial (Law, State and Telecommunications Review, 2014)
Editor-in-Chief: Prof. Marcio Iorio Aranha (University of Brasilia - BRAZIL) Editorial Board: Prof. Ana Frazao (Universidade de Brasília - BRAZIL), Andre Rossi (Utah Valley University - USA), Prof. Fabio Bassan (Universitá degli Studi Roma Tre - ITALIA), Prof. Hernán Galperin (Universidad de San Andrés - ARGENTINA), Prof. João Alberto de Oliveira Lima (Universidade do Legislativo Brasileiro - BRAZIL), Prof. Lucas Sierra (Universidad de Chile - CHILE), Prof. Luís Fernando Ramos Molinaro (Universidade de Brasília - BRAZIL), Prof. Murilo César Ramos (Universidade de Brasília - BRAZIL). e-Copyeditor: Andre Moura Gomes. ISSN: 1984-9729 EISSN: 1984-8161 Periodicity: one annual issue on May uninterrupted since May 2009 Mission/Scope/Focus: http://www.ndsr.org/SEER/index.php?journal=rdet&page=about&op=editorialPolicies#focusAndScope Submission process: authors are requested to submit their papers through the website of the University of Brasilia Center on Law and Regulation (http://www.ndsr.org/SEER/index.php). The journal adopts the double-blind peer review process. Archiving policy: LOCKSS, DOAJ and Brazil’s Senate Library. Indexation: Scopus (Elsevier); EBSCOhost research databases (EBSCO Publishing Inc.); Gale Group; AE Global Index; OAI (Open Archives Initiative) - DOAJ (Directory of Open Access Journals); WorldCat; Google Scholar; The European Library; CIEPS (Centre International d’Enregistrement des Publications en Série; SEER/IBICT. Permanent Web Identifier: LexML.